RF9 Does moving into social, intermediate and market-rent accommodation in east village (the former london 2012 olympic athletes village) improve self-rated mental health, well-being and neighbourhood perceptions? evaluation of a natural experiment. (5th September 2018) - Ram, B; Rudnicka, AR; Shankar, A; Nightingale, CM; Limb, ES; Cummins, S; Lewis, D; Corti, BG; Ellaway, A; Cooper, AS; Page, A; Whincup, PH; et al.
Abstract : Background: Evidence suggests that where we live might be an important determinant of mental health and well-being, especially amongst the more disadvantaged. However, longitudinal evidence is limited. The Examining Neighbourhood Activities in Built Living Environments in London (ENABLE London) study aimed to establish whether mental health, well-being, and neighbourhood perceptions improved among adults relocating to East Village, purposely designed for healthy active living, when compared with a control population who lived outside East Village throughout. Methods: During 2013–2015, 1278 adults seeking accommodation in East Village were recruited (participation rate 70%, n=1278/1819); 520 were seeking social housing, 524 intermediate (affordable) and 234 market-rent accommodation. Participants were followed-up after 2 years; those who moved into East Village formed the intervention group, and those who did not move to East Village controls. Self-reported mental-health (depression, anxiety), subjective well-being (life satisfaction, worthwhile, happiness), and neighbourhood perceptions (quality and crime-free) were assessed by questionnaire. Multilevel linear regression models examined change in these outcomes adjusted for age, sex, ethnicity and household (random effect), comparing those in the intervention group with controls, overall and by housing sector. Results: Of 1278 adults recruited at baseline, 877 (69%) adults were followed-up after two years; half (n=440/877) had moved to East Village. There were marginally lower levels of depression and anxiety amongst those who moved to East Village, compared with those who did not, but differences were not statistically significant. Overall levels of positive well-being (including life satisfaction, worthwhile, happiness) were marginally higher amongst participants who moved to East Village, but again differences were not statistically significant. However, increases in life satisfaction and happiness amongst those living in intermediate accommodation in East Village were stronger (p=0.01, p=0.05 respectively). The most marked differences were in neighbourhood perceptions, where sizeable increases in both quality and crime-free status were observed amongst those living in East Village compared with those who were not, overall and in each housing sector (all P values <0.01). There was also the suggestion that improvements in crime-free perceptions were stronger in the social and intermediate sectors compared to those in market-rent accommodation (test for interaction, p=0.04). Conclusion: East Village had modest effects on measures of well-being, but appreciable effects on neighbourhood perceptions. Longer-term exposure to better neighbourhoods could plausibly have beneficial effects for health, particularly for both mental health and well-being, more so among those from less privileged circumstances, who potentially have the most to gain.